The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species - Pham, Phong Huy; Ohl, Michael; Truong, Lam Xuan (Zootaxa, 2019)
The genus Chalybion Dahlbom, 1843 from northwest Vietnam is studied. Six species of the genus are recorded for the area. Of these, C. dolichothorax (Kohl, 1918) and C. gracile Hensen, 1988 are new records, whereas C. tanvinhensis sp. nov. is described as a new species. Notes on the nest of the new species and keys to both sexes of the six species reported from northwest Vietnam are provided.